2003
DOI: 10.1002/ijc.11188
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of angiogenic growth factors in squamous cell carcinomas of the head and neck

Abstract: Inhibition of angiogenesis by blocking angiogenic cytokines or their pathways has become a major target in experimental cancer therapies. This therapeutical approach requires a profound knowledge of growth factor profiles that contribute to tumor growth and progression. The respective knowledge is presently rather incomplete for head and neck squamous cell carcinomas (HNSCC). Therefore we studied expression of several angiogenic cytokines including VEGF, bFGF, PDGF-AB, PDGF-BB, G-CSF and GM-CSF in HNSCC in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 54 publications
6
103
2
2
Order By: Relevance
“…Although a previous study suggested that high TNF-a production was associated with an increased disease-free survival in nonsmallcell lung carcinoma, we did not find such an association. 37 A study by Ninck et al 38 also found a relation between the expression of growth factors (such as GM-CSF) and disease-free survival, but not by GM-CSF alone. Disease-free survival correlated with a poorer prognosis when head and neck squamous cell carcinoma simultaneously produced 3 or more growth factors.…”
Section: Discussionmentioning
confidence: 98%
“…Although a previous study suggested that high TNF-a production was associated with an increased disease-free survival in nonsmallcell lung carcinoma, we did not find such an association. 37 A study by Ninck et al 38 also found a relation between the expression of growth factors (such as GM-CSF) and disease-free survival, but not by GM-CSF alone. Disease-free survival correlated with a poorer prognosis when head and neck squamous cell carcinoma simultaneously produced 3 or more growth factors.…”
Section: Discussionmentioning
confidence: 98%
“…HNSCC cell lines 45 were cultured routinely in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal calf serum (PAA Laboratorie, Cö lbe, Germany) and 1% penicillin/streptomycin (Sigma, St Louis, MO, USA) in an atmosphere containing 5% CO 2 . 293T cell line was cultured in the same medium without antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation with primary and secondary antibodies and detection with Vectastain ELITE ABC Kit (Vector Laboratories, Burlingame, CA, USA) was carried out as described. 45 An amplification step was performed with the Tyramide Signal Amplification kit (NEL700; Perkin-Elmer, Rodgau, Germany) according to manufacturer's instructions.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…While chronic inflammation may promote tumorigenesis [5,20], the tumor cells themselves also attract immune cells through the secretion of a wide range of chemokines such as IL-8 (CXCL8 in human/CXCL2 in mouse), CCL2 (MCP-1), CCL3 (MIP-1α), CCL5 (RANTES), CXCL6 (huGCP-2), and KC (CXCL1), and cytokines such as IL-1β, IL-6, TNFα, GM-CSF, and G-CSF, thereby inducing inflammation [21][22][23][24][25][26][27][28][29][30][31][32]. Cytokines from tumors may regulate tumor growth or modify the anti-tumor immune responses [33][34][35][36].…”
Section: Niche-dependent Neutrophil Functionmentioning
confidence: 99%